2021
DOI: 10.3390/ijms22073673
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Facultative Intracellular Parasitism of Brucella

Abstract: Brucellosis is a highly prevalent zoonotic disease characterized by abortion and reproductive dysfunction in pregnant animals. Although the mortality rate of Brucellosis is low, it is harmful to human health, and also seriously affects the development of animal husbandry, tourism and international trade. Brucellosis is caused by Brucella, which is a facultative intracellular parasitic bacteria. It mainly forms Brucella-containing vacuoles (BCV) in the host cell to avoid the combination with lysosome (Lys), so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 84 publications
0
49
0
1
Order By: Relevance
“…are small (0.5-0.7 by 0.6-1.5 µm), non-motile, non-spore-forming, slowgrowing, facultative intracellular Gram-negative coccobacilli belonging to the Brucellaceae family along with the Mycoplana and Ochrobactrum spp. [1,2]. Brucellae can infect several animal species and currently comprise 12 well-classified species, 4 of which causing almost the totality of human infections: B. melitensis, B. abortus, B. suis, and B. canis, with B. melitensis being the most virulent [3].…”
Section: Laboratory Diagnosis Of Brucella Infectionmentioning
confidence: 99%
“…are small (0.5-0.7 by 0.6-1.5 µm), non-motile, non-spore-forming, slowgrowing, facultative intracellular Gram-negative coccobacilli belonging to the Brucellaceae family along with the Mycoplana and Ochrobactrum spp. [1,2]. Brucellae can infect several animal species and currently comprise 12 well-classified species, 4 of which causing almost the totality of human infections: B. melitensis, B. abortus, B. suis, and B. canis, with B. melitensis being the most virulent [3].…”
Section: Laboratory Diagnosis Of Brucella Infectionmentioning
confidence: 99%
“…Additionally, further analysis with markers of different endosomal, Golgi-and ER-derived compartments are necessary to further characterize the trafficking of the Brucellacontaining vacuole along the endosomal pathway and its ERmediated remodeling (Piersanti et al, 2015). For further reading on the survival cycle in host cells by the facultative intracellular bacteria, Brucella, please refer to the recent review by Jiao, et al (Jiao et al, 2021).…”
Section: Trafficking Of Brucella-containing Vacuole Along the Endosomal Pathwaymentioning
confidence: 99%
“…For further reading on the survival cycle in host cells by the facultative intracellular bacteria, Brucella , please refer to the recent review by Jiao, et al. ( Jiao et al., 2021 ).…”
Section: Trafficking Of Brucella -Containing Vacuole Along the Endosomal Pathwaymentioning
confidence: 99%
“…The Th1 immune response is essential for the clearance of Brucella infection, and the antimicrobial effects of pro-inflammatory cytokines, including IFN-γ and TNF-α, have been established [ 6 ]. However, Brucella can subvert the protective immune response and consequently establish a chronic infection [ 7 ]. Previous mouse model studies have shown that Brucella may modify virulence factors, such as lipopolysaccharide (LPS), proline racemase protein A (PrPA), and toll-like receptor/IL-1R (TIR)-containing protein, which in turn affect the levels of IFN-γ, TNF-α, IL-10, and TGF-β1.…”
Section: Introductionmentioning
confidence: 99%